(untitled) (Fiep Bulletin - online, 2015)
In the history of physical Education, general Anatomy and Physiology were successively considered as the principal basic sciences. They certainly still have many problems to solve, but it is generally admitted, after some years, that the essential has been reached in this field – which remains very discussible, in our opinion – and that the evolution of physical education will take place above all thanks to progress in phycho-physiology and psycho-pedagogy (which evidently includes sociological data). We are in the pedagogical era of physical Education. Among “force-ideas” in psycho-pedagogy appears very clearly that of motivation and more specially in the field which concerns us, that of “sportive motivation” that might be the starting point and the essencial “motor” of all education by means of physical activies.